Work-Family Conflict among High School Teachers in Riau: The Role of Social Factors and Malay Local Wisdom - Reizki Maharani; Firman; Syukur, Yarmis (INDONESIAN COUNSELING AND PSYCHOLOGY, 2025)
This study aims to analyze the influence of social factors and Malay local wisdom on work-family conflict (WFC) among high school teachers in Riau. The study used a quantitative descriptive approach with a sample of 231 high school teachers selected at random. Data were collected through a questionnaire measuring WFC as well as social and local cultural factors, and then analyzed using simple linear regression with SPSS. The results of the analysis indicate that social and cultural variables explain 12.4% of the variation in WFC (R Square = 0.124), with a correlation coefficient of 0.352. The F-test showed very high significance (p = 0.000), confirming that the regression model used is valid and that social and local cultural factors significantly influence WFC. The regression coefficients for social and cultural factors are negative (B = -0.397; Beta = -0.352), indicating that the stronger the influence of social values and local Malay wisdom in teachers' lives, the lower the tendency to experience WFC. Implications suggest that social support and strengthening local wisdom can be effective strategies in reducing WFC among high school teachers in Riau. This study suggests the importance of the role of schools and the government in integrating local values into educational policies to support teacher well-being.